Impact of Training and Competence on Performance moderated by the Lecturer Career Development Program in Palembang, Indonesia - Garaika, Garaika (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The existence of this study is to find out whether job training, competence and career development can affect performance, and in this study career development as a moderating variable for the training and competency variables of lecturers in Palembang, Indonesia. The population in this study were college lecturers in Palembang, Indonesia. The sample in this study was 100 respondents who were random samples from college lecturers in Palembang, Indonesia. To see the magnitude of the coefficient of influence between research variables, a survey method with a questionnaire was used. Training, competence, and career development as independent variables. While performance is the dependent variable. The results of this study indicate the significant positive effect of training on career development, the significant positive effect of competence on career development, the insignificant positive effect of training on performance, the significant positive effect of competence on performance and the significant positive effect of career development on performance. Higher education institutions in Palembang, Indonesia are expected to provide clarity on the career development of lecturers through (mutation, selection, placement, education, and training), then consistently given training through (seminars) by bringing in experienced instructors, providing material and quality methods, as well as enhancing the competence of lecturers to increase their knowledge, understanding, abilities, skills, attitudes and interests in accordance with their fields of science. Key Word : Training, Competence, Career Development, Performance